Minimizing femoral artery access complications during percutaneous coronary intervention: A comprehensive review. Issue 1 (10th March 2014) - Lee, Michael S.; Applegate, Bob; Rao, Sunil V.; Kirtane, Ajay J.; Seto, Arnold; Stone, Gregg W.
<x xml:space="preserve">Abstract</x> Major bleeding complications after percutaneous coronary intervention (PCI) increase patient morbidity, prolong the hospital stay and costs, and are associated with reduced survival. Transfemoral access is still preferred at many centers given its familiarity and ease of use and is necessary in cases where large bore access is needed. Multimodality imaging with fluoroscopy, ultrasonography, and angiography can facilitate proper puncture of the common femoral artery. A proper technique (which includes femoral artery puncture and vascular access site closure) associated with adequate pharmacotherapy (both during PCI and peri‐procedural, for the treatment of the underlying coronary artery disease) has been shown to reduce the risk of bleeding and vascular complications associated with femoral artery access. Avoiding the use of arterial sheaths >6 French may further reduce the risk of bleeding. Data with vascular closure devices as a bleeding avoidance strategy are evolving but when used appropriately may further reduce the risk of bleeding and vascular access complications, and in this regard are synergistic with bivalirudin. Randomized trials to confirm these recommendations are needed. © 2014 Wiley Periodicals, Inc.